Hydrochemical Characteristics and Water Quality Assessment of a Zn-Pb Mine Waters in Yunnan Southwest China. (January 2019) - Cheng, Xianfeng; Huang, Qianrui; Danek, Tomas; Marschalko, Marian; WufuQi,; Yang, Shuran; Zou, Liling; Zhao, Xinliang; Xiang, Yungang
Abstract: Water samples (rivers, streams, mine adits, tailings ponds) from Jinding zinc-lead polymetallic mining area and Bi River Basin were analysed for 32 indicators including major hydrochemical components and heavy metals. The correlation analysis of water chemical parameters and Gibbs diagram show that the water composition of the Bi River is influenced by human activities in addition to the rock weathering. In the streams, the main cations and anions are derived from the rock weathering of formations rich in gypsum, calcite and dolomite. Nemerow comprehensive pollution index method was performed to evaluate water quality. The water of streams and one pond is clean. Mine adits water pollution level is medium-heavy pollution. The water samples flowing through the mining area and from tailings ponds are heavy polluted.